Driving Natural Killer cells toward the melanoma tumor battlefield: Autophagy as a valuable therapeutic target. (3rd August 2018) - Noman, Muhammad Zaeem; Paggetti, Jerome; Moussay, Etienne; Berchem, Guy; Janji, Bassam
ABSTRACT: Natural Killer (NK) cell-based cancer immunotherapies were often disappointing in the clinic mostly due to insufficient NK cell infiltration into tumors. We found that targeting autophagy induced a massive infiltration of NK cells into melanoma tumors. These findings highlight autophagy inhibition as a cutting-edge approach to fully exploit the anti-tumor properties of NK cells in a wide variety of cancer patients.